Healthcare related transmission of Pneumocystis pneumonia: From key insights toward comprehensive prevention. Issue 5 (28th June 2018) - de Boer, Mark G. J.; Walzer, Peter D.; Mori, Shunsuke
Abstract: In at risk populations, Pneumocystis pneumonia (PCP) may occur as a solitary event as well as in a cluster‐ or outbreak setting due to interpatient transmission of Pneumocystis jirovecii . Despite the data and insights obtained from studies of outbreaks of PCP, the development and implementation of comprehensive recommendations for the prevention of healthcare related transmission of P. jirovecii have been delayed. Both optimization of chemoprophylaxis strategies as well as combination with prudent use of isolation precautions are warranted to achieve this goal. The rationale of the available measures for the prevention of PCP should be viewed in the context of what is currently known about the complex biology and epidemiology of P. jirovecii . From there, phased but practical prevention strategies can be deducted to balance the efforts, costs and negative consequences of chemoprophylaxis and isolation precautions with the beneficial effect of preventing healthcare related transmission of P. jirovecii and development of PCP.